2021
DOI: 10.3390/ijerph18136879
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Lead Exposure and Allostatic Load on Cardiovascular Disease Mortality—A Preliminary Study

Abstract: This study explores the combined effect of lead (Pb) exposure and an index of chronic physiological stress on cardiovascular disease mortality using data from the National Health and Nutrition Examination Survey (NHANES) 1999–2008 linked to 1999–2014 National Death Index data. Chronic physiological stress was measured using the allostatic load (AL) index, which was formed by analyzing markers from the cardiovascular, inflammatory, and metabolic systems, with Pb levels, assessed using blood lead levels (BLL). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 71 publications
(81 reference statements)
1
14
0
Order By: Relevance
“…The association between AL and gender was significant; this was similar to the findings of Juster et al and of others [ 34 , 35 ], which indicated that males have higher AL levels than females.…”
Section: Discussionsupporting
confidence: 91%
“…The association between AL and gender was significant; this was similar to the findings of Juster et al and of others [ 34 , 35 ], which indicated that males have higher AL levels than females.…”
Section: Discussionsupporting
confidence: 91%
“…Lead (Pb) is a widespread and harmful environmental toxicant [1][2][3] that causes adverse health effects in children, particularly neurological and neurobehavioral deficits, lower IQ, slowed growth and anemia [4][5][6][7]. In addition, the health effects of Pb over the life course have been documented, including adverse effects on the cardiovascular [8,9], renal and hepatic systems [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Potential covariates may confound the association between BLL and AAC were summarized in our multivariable-adjusted models based on previous studies (26,(30)(31)(32). Continuous variables in our study included age, systolic blood pressure (SBP), diastolic blood pressure (DBP), serum creatinine, serum cotinine, hemoglobin A1c, serum uric acid, serum calcium, serum phosphorus, total cholesterol, and total 25hydroxyvitamin D. Categorical variables included gender, race, education level, body mass index (BMI), hypertension, and diabetes.…”
Section: Covariatesmentioning
confidence: 99%